Farm-level effects of irrigation system design and operation problems - Tabbal, D. F.; Bhuiyan, S.I.; Murray-Rust, Hammond (1986)
The paper discusses the interrelationship of design (and construction), operation, and performance of irrigation systems. Specifically, it (1) describes the farm-level effects of design (and construction) and operation on the performance of irrigation systems; (2) identifies the factors leading to ineffective use of farm-level facilities by farmers; and (3) recommends additional criteria for the design and operation of irrigation systems. Arguments from Philippine case studies that evaluated alternative designs of farm-level facilities and approaches to improve equity in water allocation and distribution in a modern traditionally designed run-of-the-river, reservoir-backed, and pump-based irrigation systems are used.